Laughing Through Heritage: The Role of Aceh Pungo in Sustaining Acehnese Identity - Athifa Radella Tabina; Nuriza Dora (Nurul Jadid University, 2025)
This research aims to understand the role of Aceh Pungo in maintaining the cultural identity of the Acehnese people in the midst of globalization and modernization. The term